EFG1, Everyone’s Favorite Gene in Candida albicans: A Comprehensive Literature Review - Glazier, Virginia E. (Frontiers in Cellular and Infection Microbiology, 2022)
Candida sp. are among the most common fungal commensals found in the human microbiome. Although Candida can be found residing harmlessly on the surface of the skin and mucosal membranes, these opportunistic fungi have the potential to cause superficial skin, nail, and mucus membrane infections as well as life threatening systemic infections. Severity of infection is dependent on both fungal and host factors including the immune status of the host. Virulence factors associated with Candida sp. pathogenicity include adhesin proteins, degradative enzymes, phenotypic switching, and morphogenesis. A central transcriptional regulator of morphogenesis, the transcription factor Efg1 was first characterized in Candida albicans in 1997. Since then, EFG1 has been referenced in the Candida literature over three thousand times, with the number of citations growing daily. Arguably one of the most well studied genes in Candida albicans, EFG1 has been referenced in nearly all contexts of Candida biology from the development of novel therapeutics to white opaque switching, hyphae morphology to immunology. In the review that follows we will synthesize the research that has been performed on this extensively studied transcription factor and highlight several important unanswered questions.